2017
DOI: 10.3389/fpsyt.2017.00258
|View full text |Cite
|
Sign up to set email alerts
|

A Biomarker to Differentiate between Primary and Cocaine-Induced Major Depression in Cocaine Use Disorder: The Role of Platelet IRAS/Nischarin (I1-Imidazoline Receptor)

Abstract: The association of cocaine use disorder (CUD) and comorbid major depressive disorder (MDD; CUD/MDD) is characterized by high prevalence and poor treatment outcomes. CUD/MDD may be primary (primary MDD) or cocaine-induced (CUD-induced MDD). Specific biomarkers are needed to improve diagnoses and therapeutic approaches in this dual pathology. Platelet biomarkers [5-HT2A receptor and imidazoline receptor antisera selected (IRAS)/nischarin] were assessed by Western blot in subjects with CUD and primary MDD (n = 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
2
0
1
Order By: Relevance
“…According to these results and previously published research [ 44 ] it can be presumed that the biochemical basis of induced-MDD differs from primary-MDD. The neurobiological basis for induced depression in CUD does not seem to be primarily mediated by 5-HT dysfunction and other neurotransmitter pathways may be involved.…”
Section: Discussionsupporting
confidence: 75%
“…According to these results and previously published research [ 44 ] it can be presumed that the biochemical basis of induced-MDD differs from primary-MDD. The neurobiological basis for induced depression in CUD does not seem to be primarily mediated by 5-HT dysfunction and other neurotransmitter pathways may be involved.…”
Section: Discussionsupporting
confidence: 75%
“…Because there was a strong association between alterations in the plasma expression of certain inflammatory mediators and comorbid MDD, we extended our study in CUD patients diagnosed with primary and cocaine-induced MDD. In fact, the differentiation between primary and substance-induced MDD in dual pathology is a field of study to be explored, and a recent research has showed that platelet IRAS/nischarim (I 1 -Imidazoline receptor) could discriminate between primary MDD and cocaine-induced MDD in CUD patients [ 51 ]. In our study, we have observed differences in the plasma expression of CCL11 and CXCL12 according to the type of MDD.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, its expression has been identified in several tissues ( 5 , 7 ). The roles of Nischarin in humans include serving as a neuroprotective protein that regulates neuronal migration ( 7 ), a regulator of brain function ( 8 , 9 ), a regulator of blood pressure ( 10 ) and a tumor suppressor of ovarian and breast cancer ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%